Hypofractionated radiotherapy in the management of prostatic cancer - Cury, Fábio Luís Biagini (2004)
Radiotherapy remains a standard treatment option for localized prostate cancer. Over the last few years, improvement of treatment results with the use of higher total doses of irradiation has been extensively studied, particularly since the development of modern and more precise planning and treatment systems. Recently, the interest for the use of hypofractionated irradiation schedules in prostate cancer has increased. Such renovated interest arrives from newer radiobiological data which suggest that the á/â ratio for prostate cancer is much lower than previously estimated. Thus, hypofractionation regimens appear to be an attractive therapeutic option for the treatment of these tumors given that an improved therapeutic index may be achieved by changing the daily radiotherapy dose. This paper critically review the use of hypofractionation in the management of prostatic cancers.